Patterns of Benthic Communities in Arctic Fjords (Novaya Zemlya Archipelago, Kara Sea): Resilience vs. Fragility - Udalov, Alexey; Chikina, Margarita; Chava, Alexandra; Vedenin, Andrey; Shchuka, Sergey; Mokievsky, Vadim (Frontiers in Ecology and Evolution, 2021)
Despite a large number of studies, a detailed overall picture of benthic communities zonation in the Arctic fjords is currently lacking. Our study aimed to find out whether there is a universal model for the distribution of benthic communities based on the structural features of the fjords. We examined benthic macrofaunal communities in fjords with various environmental settings on the eastern coast of Novaya Zemlya Archipelago, Kara Sea. The material was collected during five cruises undertaken from 2013 to 2016. A total of 50 stations located in the five fjords were taken. In all five fjords, macrofauna had a similar composition assembled from a regional species pool, with a predominance of species tolerant to glacial sedimentation and fluctuations in temperature and salinity. Benthic communities changed consistently along the axis of the bay from the outer slope to the inner parts. Biodiversity and quantitative characteristics of the macrofauna decreased along the environmental gradient related to terrigenous and glacial runoff, consistent with patterns reported in other studies of Arctic glacial fjords. The most impoverished communities were dominated by bivalve Portlandia arctica and isopod Saduria sabini. At the same time, fjord walls and sills, characterized by low sedimentation rates, strong currents and the presence of ice-rafted debris, were inhabited by patchy distributed benthic communities dominated by species confined to hard substrates. In general, the distribution of communities corresponded to five zones: depleted inner periglacial areas, the upper subtidal belt with stony substrates, deep inner semi-isolated basin, outer non-isolated basins and upper slope transitioning to lower slope. Our study can provide a reference point for monitoring changes in fjord ecosystems in response to climate change and the potential impact of human activities.